2007
DOI: 10.1021/ef700400j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coal Composition and Operating Conditions on the Release of Alkali Species During Combustion of Hard Coal

Abstract: In solid fuel conversion systems, the release of alkali species can cause severe problems such as fouling, slagging, corrosion, and erosion. Especially in future coal-fired combined cycle processes such as pressurized pulverized coal combustion (PPCC), alkali species can cause corrosion of the gas turbine blading. In order to solve these problems, detailed information about the alkali release is required. In this work, the influence of coal composition and operating conditions on the release of alkali species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Most likely, the extra amount of Cl with increasing turkey manure share of the blends can effectively enhance the release of both 58 NaCl + and 74 KCl + , which leads to decreasing release of 36 HCl + . A likely explanation for the positive deviation between the calculated and the experimental data of 58 NaCl + for turkey manure hard coal blends can be given by the exchange reaction of Na-aluminosilicates with K as published for hard coal and lignite by Oleschko et al 16,17 ■ MEAT BONE AND COAL…”
Section: ■ Turkey Manure and Coalmentioning
confidence: 88%
“…Most likely, the extra amount of Cl with increasing turkey manure share of the blends can effectively enhance the release of both 58 NaCl + and 74 KCl + , which leads to decreasing release of 36 HCl + . A likely explanation for the positive deviation between the calculated and the experimental data of 58 NaCl + for turkey manure hard coal blends can be given by the exchange reaction of Na-aluminosilicates with K as published for hard coal and lignite by Oleschko et al 16,17 ■ MEAT BONE AND COAL…”
Section: ■ Turkey Manure and Coalmentioning
confidence: 88%
“…To predict the fouling and slagging tendencies of the biomass experimental fuels, in order to study possible countermeasures to these phenomena [34][35][36], some research has developed a series of numerical correlations to assign a value to the proportion of certain components to others. These correlations are the so-called fouling indexes [37][38][39][40].…”
Section: Deposition Indexesmentioning
confidence: 99%
“…A lot of research has shown that the slagging and fouling on heating surfaces during coal combustion are usually related to alkali metal elements Na and K [16][17][18][19][20][21][22]. As shown in Table 4, the ash in the flue gas exhausted from the ferrosilicon electric furnace has high Na and K contents, which leads to easy slagging and fouling.…”
Section: Slagging Mechanismmentioning
confidence: 99%